Pengaruh Overconfidence Bias dan Herding Bias terhadap Investment Intention pada Generasi Z - Dave Reynard; Njo Anastasia (Bulletin of Community Engagement, 2024)
This study explores the investment behavior of Generation Z, specifically focusing on individuals aged 18-27, who are in the emerging adult phase. This study aims to look at the effect of overconfidence bias and herding bias on the investment intention of generation Z in the emerging adult phase. This research uses associative methods with a quantitative approach. The technique and data analysis used is the Structural Equation Modeling (SEM) Partial Least Square (PLS) approach with the SmartPLS version 4 application program. When testing hypotheses, research uses an error tolerance of 10%. The results of 100 respondents in this study show that overconfidence bias has a significant effect on investment intention in generation z emerging adult phase while herding bias does not have a significant effect on investment intention in generation z emerging adult phase. The effect of the variables overconfidence bias and herding on investment intention is 40.9%. The results of this study are expected to provide education about the influence of overconfidence bias and herding bias on generation Z's investment intention and can be a reference for further research.